Landscape resource management for sustainable crop intensification - Anantha, K. H.; Garg, K. K.; Singh, R.; Akuraju, V.; Dev, I.; Petrie, C.A; Whitbread, Anthony M.; Dixit, S. (IOP Publishing, 2022)
Crop intensification is required to meet the food demands of an increasing population. This paper presents data from three paired scaling-up initiatives to compare the benefits of landscape-based interventions over individual plot-level interventions using evidence generated in the Indian semi-arid tropics. A range of soil and water conservation interventions were implemented in a decentralized manner following the landscape-based approach. The plot-level approach focused only on balanced fertilizer application and improved crop cultivars while the landscape-based interventions primarily addressed moisture availability, which was the key to reducing risks of crop failure besides aiding productivity gain and enhanced land and water-use efficiency. These interventions have additionally harvested 50–150 mm of surface runoff and facilitated groundwater recharge in 550–800 mm rainfall zones. Individual plot-level interventions also improved the crop yield significantly over the control plots. However, crop intensification was not achieved due to limited moisture availability. Landscape-based interventions produced 100%–300% higher crop production per year, greater income generation (>100%), and improved water productivity. Landscape-based interventions were also found to be beneficial in terms of reducing soil loss by 75%–90% and improving base flow availability additionally by 20–75 d in a year compared to untreated watersheds. With increased moisture availability, fallow lands in respective watersheds have been utilized for cultivation, thereby enhancing crop intensification. The findings of the study provide critical insights into the design of approaches suitable for scaling-up projects in order to both create impact and target the United Nations Sustainable Development Goals.